ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UTANG LUAR NEGERI DI INDONESIA - Rieski Prodeo Patria; Syamsir Nur (Universitas Halu Oleo, 2015)
This study aims to determine and analyze the factors that affect foreign debt in Indonesia either partially or simultaneously. The variables used in this research are domestic revenue (PDN), total central government expenditure (GPUSAT) and Budget Deficit (DA) and total Foreign Debt in Indonesia. The data used are secondary data sourced from Bank Indonesia, Indonesian Central Bureau of Statistics and Ministry of Finance. Analyzer used is Multiple Linear Regression analysis with OLS (Ordinary Least Square) method and using E-Views8 Program period research aid with year 1995-2015. The results show that simultaneously government revenues, government expenditure and budget deficit have a significant effect on foreign debt in Indonesia. With a probability value of F-statistics 0,000000. From the regression results obtained value of adjusted coefficient (R2) of 0.9781, this illustrates that the independent variables are together able to provide an explanation of the dependent variable of 97.81 percent. The remaining 2.19 percent is influenced by other variables outside the model. Partially, government revenue has significant and negative effect, government expenditure has a significant and positive impact on foreign debt in Indonesia. While the budget deficit has no significant and negative effect on foreign debt in Indonesia.